Irregular Immigration in a Global Context : Drivers, Impacts, and Policy Solutions - Multan, Anastasiya; Shymanska, Kateryna; Agustina, Shirley Basauli; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The thesis "Irregular Immigration in a Global Context: Drivers, Impacts, and Policy Solutions" explores the complex issue of irregular migration. It analyzes key drivers, including economic decline, economic inequality, and social networks, which influence individuals' decisions to migrate irregularly. To investigate these drivers in more detail, the thesis examines the correlation between the number of irregular migrants detected in the EU between 2015 and 2023 and the Fragile State Index (FSI). Additionally, the thesis studies both the positive and negative impacts of irregular migration on host countries, highlighting that while it can address labor shortages in certain sectors, it can also exacerbate social inequality and create integration challenges. The research also emphasizes the national policies and regional agreements of the case countries (the USA, the EU, and Australia), as well as the role of international organizations like the UNHCR and IOM in managing irregular migration.
Vedoucí práce: Kateryna Shymanska
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses